2021
DOI: 10.1038/s41598-021-88953-7
|View full text |Cite
|
Sign up to set email alerts
|

Feeding experiments on Vittina turrita (Mollusca, Gastropoda, Neritidae) reveal tooth contact areas and bent radular shape during foraging

Abstract: The radula is the food gathering and processing structure and one important autapomorphy of the Mollusca. It is composed of a chitinous membrane with small, embedded teeth representing the interface between the organism and its ingesta. In the past, various approaches aimed at connecting the tooth morphologies, which can be highly distinct even within single radulae, to their functionality. However, conclusions from the literature were mainly drawn from analyzing mounted radulae, even though the configuration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 54 publications
0
33
0
Order By: Relevance
“…For example, the direct inference simply from tooth shape [32], e.g. interpreting from a broad cusp directly its ability to loosen food items, is far too speculative, especially since experimental approaches revealed that not all teeth necessarily interact with the substrate [33], but still contribute to the overall radular function by, for example, reinforcing the spanned radula [34].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…For example, the direct inference simply from tooth shape [32], e.g. interpreting from a broad cusp directly its ability to loosen food items, is far too speculative, especially since experimental approaches revealed that not all teeth necessarily interact with the substrate [33], but still contribute to the overall radular function by, for example, reinforcing the spanned radula [34].…”
Section: Introductionmentioning
confidence: 99%
“…Second, the configuration of the radula during foraging is not the same as that of mounted radula [34]: molluscs are capable of bending, twisting and flapping their radula, as previously documented by studying foraging gastropods through glass surfaces [35][36][37][38][39][40][41][42] and/or by analysing feeding tracks [13,35,36,39,[43][44][45][46][47][48][49][50]. However, feeding tracks are difficult to interpret and additionally, only teeth, which were pressed into the substrate forcefully, rather leave a mark and teeth that do not interact or interact with the low force do not leave tracks [34]. Experiments, making interaction of teeth with substrate clearly visible, are without doubts highly desired, as the knowledge about precise contact areas of teeth could further contribute to determining tooth functionality, because these areas function as load-transmitting regions.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Summary of the preferred feeding substrate with the references, the previously assigned feedings substrate category (mixed, solid, and soft; from Krings et al,Krings, 2021), and previously determined Young's moduli (GPa) of the distinct tooth parts (with collection number and quantity of analysed specimens, and analysed tooth parts (data fromKrings et al, 2019, 2021b are provided for each species studied. Geometrical variables of radulae (widt and volume of the model) necessary to determine the nominal force for each species.…”
mentioning
confidence: 99%